PENGEMBANGAN BUKU TEKS MENULIS ARGUMENTASI BERDASARKAN POLA PENALARAN ARGUMENTATIF - Syaifudin, Ahmad; Pratama, Hendi (Jurnal Penelitian Pendidikan, 2013)
This paper aimed to establish the development of textbooks written argumentation based reasoning pattern argumentaif. Through R & D study design, this study produced findings that textbooks written arguments used in the current school textbooks covering publications Pusbuk (BSE), a textbook published by the private sector, and textbooks terbita MGMP. The entire book has a structure of the same material, ie understanding (concept), characteristic / criteria, and the steps are written arguments like writing in general, (2) the development of text books written arguments through support ICT based argumentative reasoning patterns in high school students are prepared based on the principle of development, the provisions of the development, and the steps / procedure development. The principle of development used is based on the principle of coherence, relevance, consistency, and adequacy. The provision of development used whether they reference the development, content, organization of material, material development, presentation, and evaluation. In the meantime, the steps in preparing to write argumentative texts based argumentative reasoning patterns include analyzing SK and KD, determine indicators of achievement, identify basic theories used, compiling textbooks, textbook editing, and verification of eligibility, and (3) The development of textbooks written arguments based argumentative reasoning patterns assessed both by teachers and students of high school and fit for use in learning at school.